Недійсність відступного - Рассказова, В. В.; Rasskazova, V. V.; ORCID: https://orcid.org/0000-0003-0887-4880 (Аналітично-порівняльне правознавство. - 2021. - № 4. - С. 75-79, 2021)
Проаналізовано правове регулювання недійсності правочину про припинення зобов’язання переданням відступного. Визначено підстави, із якими закон пов’язує недійсність відступного. Виокремлено особливості укладення договору про відступне, які можуть впливати на правомірність зазначеної угоди. Окреслено помилки у розумінні природи та особливостей механізму припинення зобов’язання переданням відступного, які зумовлюють в подальшому визнання таких правочинів недійсними.

The scientific article is devoted to the invalidity of the agreement of the retreat, determining the grounds on which the law connects the invalidity of the agreement, as well as highlighting the features of the agreement retreat, which may further affect the legality of the transaction. It is noted that the current legislation does not provide special grounds for recognizing the agreement of the retreat as invalid, which makes it necessary to be guided by the general requirements, compliance with which is necessary for the validity of the transaction. In addition to the general grounds for invalidity applicable to all types of transactions the analysis of the grounds for invalidity of the agreement of the retreat should be based on the essence of the institution of the retreat, which in accordance with the legal definition of this concept embodies the principle of freedom of contract, the essential terms of the contract, which constitute the content of the relevant legal relationship. It is the legal features of the institution of the retreat, that determine the existence of other features that determine the agreement as disputed. In the example of court cases and the most common in contractual practice issues of application of the institution of the retreat, outlined errors in understanding the nature and features of the mechanism of termination of the obligation to transfer the assignment, which lead to further recognition of such transactions invalid. Attention is paid to certain problematic issues and requirements of current legislation, failure to take into account which the parties in concluding the of the agreement of the retreat may lead to further invalidation of the agreement, in particular, the subject of the retreat should be only the property, property rights, etc. which belong to the debtor at the time of the transaction. The agreement of the retreat under which the debtor transfers to the creditor property that does not belong to him or an object that does not meet certain conditions of the agreement does not give rise to legal consequences in the form of civil rights and obligations under the contract. In other words, the creditor has no the legal basis for the acquisition of rights to such property and the principal obligation is not terminated in such a case.

Проанализировано правовое регулирование недействительности сделки о прекращении обязательства передачей отступного. Определены основания, с которыми закон связывает недействительность отступного. Выделены особенности заключения договора об отступном, которые могут влиять на правомерность указанного соглашения. Обозначены ошибки в понимании природы и особенностей механизма прекращения обязательства передачей отступного, которые обуславливают дальнейшее признание таких сделок недействительными.
Invalidity of the retreat
Рассказова, В. В. Недійсність відступного [Електронний ресурс] / Рассказова В. В. // Аналітично-порівняльне правознавство. - 2021. - № 4. - С. 75-79. - Режим доступу: http://app-journal.in.ua/wp-content/uploads/2022/03/15.pdf.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; відступне; retreat; отступное; недійсність правочину; invalidity of the deed; недействительность сделки; недійсність відступного; invalidity of the retreat; недействительность отступного; припинення зобов’язання; termination of the obligation; прекращение обязательства; угода про відступне; agreement of the retreat; соглашение об отступном; правове регулювання; legal regulation; правовое регулирование